Perlindungan Hak Cipta dalam Kasus Penggunaan Lagu SKJ88 Tanpa Izin Oleh O Shop (Studi Kasus Putusan Nomor 991/Pdt.Sus-HKI/2022) - Basuki Wicaksono, Agung (UNES Law Review, 2023)
This research aims to analyze the copyright infringement of the song SKJ88 by O Shop in the context of Law No. 28 of 2014 on Copyright in Indonesia, based on Decision Number 991/Pdt.Sus-HKI/2022. The main focus is on the exclusive rights of the creator, including moral and economic rights, as well as the implications of using the song without permission in commercial advertisements. This study uses a normative method, focusing on legal regulations and relevant legal cases. The author explores licensing aspects in copyright, including various types of licenses such as Mechanical Rights, Performing Rights, and Synchronization Rights, as well as the importance of licensing agreements in managing the economic rights of creators. This case highlights the importance of copyright protection in a commercial context and the legal consequences of copyright infringement. The author concludes that the legal considerations by the Panel of Judges in this case are appropriate and in accordance with the Copyright Law. The decision strengthens the principle of the creator's exclusive rights, acknowledges copyright infringement through the unauthorized use of the song, and applies appropriate sanctions, including compensation for copyright infringement.